2008
DOI: 10.1097/rct.0b013e318136e194
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement Characteristics of Ultrasmall Superparamagnetic Iron Oxide Particle Within the Prostate Gland in Patients With Primary Prostate Cancer

Abstract: Enhancement of the prostate gland after USPIO administration may be associated with primary prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
4
0
2
Order By: Relevance
“…This study also confirmed the efficiency of imaging techniques especially MRI for PCa diagnosis [85]. Previously, Li, Chao-Shiang et al used USPION as a contrast agent in MRI to detect PCa in the primary stage [86]. In this study, 60 patients were included where central zones (CZ) and peripheral zones (PZ) of prostate were assayed by T2-and T2*-weighted MRI in association with USPION-enhanced MRI.…”
Section: Detection Of Metastasessupporting
confidence: 75%
“…This study also confirmed the efficiency of imaging techniques especially MRI for PCa diagnosis [85]. Previously, Li, Chao-Shiang et al used USPION as a contrast agent in MRI to detect PCa in the primary stage [86]. In this study, 60 patients were included where central zones (CZ) and peripheral zones (PZ) of prostate were assayed by T2-and T2*-weighted MRI in association with USPION-enhanced MRI.…”
Section: Detection Of Metastasessupporting
confidence: 75%
“…28 However, in the glandular peripheral zone and anterior gland, DCE-MRI can be quite helpful in identifying lesions that are not suspected on T2W images. 29 Li et al 30 demonstrated the association between prostate enhancement after USPIO particle administration and tumor grade in 60 patients with primary prostate cancer; the degree of enhancement (negative contrast in the case of USPIOs) correlated positively with tumor grade. DCE-MRI alone has reported sensitivity and specificity ranges of 46–96% and 74–96%, respectively, for detection of tumor lesions, but, as always, these ranges are highly dependent on patient selection, technique and diagnostic criteria.…”
Section: Current Imaging Modalitiesmentioning
confidence: 99%
“…Ultrasmall superparamagnetic iron oxide-enhanced MRI can also be used in the diagnosis of primary prostate cancer (57). In patients with prostate cancer, ultrasmall superparamagnetic iron oxide-enhanced MRI may demonstrate a characteristic decrease in the signal-to-noise ratio of the prostate gland.…”
Section: Goldmentioning
confidence: 99%